High-Level Forum on the Health Millennium Development Goals : selected papers 2003-2005 - Cahill, Kathy...[et al.] (WHO GenevaCH, 2006)
Presents an overview of the analysis and work undertaken throughout the life of the High Level Forum on the key policy areas of concern to the health sector.